Digitizing Public Archives in Ghana: What is PRAAD’s Problem? - Fuseini, Azindow Bawah (Bobcatsss, 2023)
Knowledge of the past is necessary to shape the present and to predict the future. Archival materials are evidence of what happened in the past. Archives connect past to the future by informing future generations what had happened. Individuals, organisations and governments use archives for varied purposes. Owing to the intrinsic value of archives, society is required to preserve them and it has been doing that over the years. However, the advancement of technology is putting demand on institutions responsible for preserving archives to digitize their resources and operations. The argument is that digitized archives are more appealing, have the potential to be preserved for longer period and could easily be accessed from anywhere, anytime. In response to the demand, many countries especially in the developed world have digitized their public archives. In Ghana, Public Records and Archives Administration Department is responsible for protecting, preserving and making public archives accessible to users. The department is responsible for digitizing public archives in Ghana but those materials are still not digitized. The purpose of this study was to investigate the problems faced by PRAAD in digitizing public archives. The main question the study sought to answer was: What problems prevent PRAAD from digitizing public archives in Ghana? To answer the above question, the study employed a case study strategy and a questionnaire method to collect data from 23 PRAAD staff, at the head office in Accra. The data collected were analysed using descriptive statistical methods and with the aid of SPSS. The study revealed that the main challenge by PRAAD in digitizing publics is lack of funds and appropriate technologies. So, to overcome the challenge PRAAD should be supported with the needed funds and the necessary ICT infrastructure.